IMPLEMENTASI MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING PADA MATA PELAJARANPENDIDIKAN AGAMA ISLAM - Uswatun Hasanah; Syafruddin Nurdin; Marhamah Nurdin; Asraf Kurnia (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
Islamic Religious Education in public schools often holds a less strategic position because learning practices are still dominated by conventional, lecture-based methods that are one-directional, monotonous, minimally interactive, and unable to provide meaningful learning experiences. Several studies report that the lecture method produces only about 11% learning meaningfulness, which contributes to low motivation, limited student engagement, and weak relevance between instructional content and students’ real-life contexts. This situation contrasts with the principles of Contextual Teaching and Learning (CTL), which emphasize connecting learning materials with everyday life as a basis for knowledge construction. This study aims to describe the concept, characteristics, and implementation of the CTL learning model in Islamic Religious Education as a more participatory and meaningful alternative approach. The research employed a qualitative method through a literature review. The findings indicate that CTL positions students as active learners through activities of discovering, connecting, and reflecting on knowledge in real-world contexts. The application of CTL in PAI not only strengthens the cognitive domain but also develops students’ affective, social, and moral domains. These results suggest that CTL has strong potential to enhance learning motivation and active participation, making it a strategic approach for contextual and character-oriented PAI learning.